EFFECTS OF BUPROPION ON COGNITIVE PERFORMANCE DURING INITIAL TOBACCO ABSTINENCE - Perkins, Kenneth A. (2013)
BACKGROUND: Bupropion may aid tobacco abstinence by quickly relieving symptoms of nicotine withdrawal, perhaps including impaired cognitive performance. We examined whether bupropion would attenuate abstinence-induced cognitive deficits on the first day of a brief quit attempt, when smokers are most likely to relapse. METHODS: Smokers (N=24) with high quit interest were recruited for a within-subjects cross-over test of bupropion vs placebo on ability to abstain during separate short-term practice quit smoking attempts. After introduction to working memory (N-back) and sustained attention (continuous performance task; CPT) tasks during the pre-quit smoking baseline, performance on these tasks was assessed after abstaining overnight (CO<10 ppm) on the first day of each quit attempt, while on bupropion and on placebo. RESULTS: Compared to placebo, bupropion after abstinence improved correct response times for working memory (p=.01 for medication by memory load interaction) and for one measure of sustained attention (numbers, but not letters; p<.05). DISCUSSION: Bupropion may attenuate some features of impaired cognitive performance due to withdrawal on the first day of a quit attempt. Future studies could examine whether this effect of bupropion contributes to its efficacy for longer-term smoking cessation.